2015
DOI: 10.3329/bmrcb.v40i3.25232
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Psychological Empowerment on Organizational Commitment among Medical Employees in a Hospital Setting

Abstract: Introduction: people within organizations are a key factor for efficiency. Thus employee empowerment has become a popular management strategy. The study aimed to investigate the relationship between psychological empowerment and organizational commitment among medical staff of a hospital in Zahedan city. Methods: This cross sectional study was carried out in 2013. A random sample of 172 medical employees in Khatam-ol-Anbia hospital at Zahedan city was selected and responded to items of the questionnaires using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
5
1
Order By: Relevance
“…Among the studies that examine the subconstructs of psychological empowerment on nurses' organizational commitment, some found that only 'meaning' had a statistically reliable relationship with the outcome (Abili & Nastezaie, 2009). In contrast, other research (Kebriaei et al, 2014) found that other empowerment subcomponents were significantly related to respondents' organizational commitment (only 'competence' was not significantly associated with the outcome). Related, in our study examining similar measures-though among a sample of licensed practical nurses-we found that with the exception of 'competence', the remaining psychological empowerment subscales were positively associated with organizational commitment.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…Among the studies that examine the subconstructs of psychological empowerment on nurses' organizational commitment, some found that only 'meaning' had a statistically reliable relationship with the outcome (Abili & Nastezaie, 2009). In contrast, other research (Kebriaei et al, 2014) found that other empowerment subcomponents were significantly related to respondents' organizational commitment (only 'competence' was not significantly associated with the outcome). Related, in our study examining similar measures-though among a sample of licensed practical nurses-we found that with the exception of 'competence', the remaining psychological empowerment subscales were positively associated with organizational commitment.…”
Section: Discussioncontrasting
confidence: 72%
“…Researchers have linked psychological empowerment to increases in nurses' job satisfaction (Laschinger et al, 2001;Ouyang et al, 2015) and decreases in their levels of job strain (Laschinger et al, 2001), for example. Other researchers have connected the psychological empowerment of nurses and other medical personnel to greater levels of organizational commitment (Abili & Nastezaie, 2009;Albasal et al, 2022;Kebriaei et al, 2014Kebriaei et al, , 2016.…”
mentioning
confidence: 99%
“…In a study conducted by Shoorideh et al (24), nurses also had a moderate level of organizational commitment. However, the results of the study conducted by Kebriaei et al (25), Larber and Savis (6), Carmen (26), and Siew (27) reflect high commitment levels of nurses. There seems to be some important reasons for the lack of organizational commitment of nurses in the present study and in the majority of health centers in our country, including low number of nurses, increased work pressure, lack of appropriate benefits, and lack of proper working relationship with managers and physicians, which eventually lead to reduced level of organizational commitment.…”
Section: Discussionmentioning
confidence: 95%
“…Tool for part four was adapted from organizational commitment questioners of studies of Jaros which was initially developed and validated by Meyer and Allen (20). Tool for part ve was adapted from Multi factor Leadership Questionnaire (MLQ) of studies of Mora C. and Ticlau T., which was rstly developed and validated by Bass and Avolio (21). Lastly, a tool for part six was adapted from studies of Ambad S and Bahron, which was initially developed and validated by Spreitzer (22).…”
Section: Data Collection Toolmentioning
confidence: 99%